A Pilot Study Verifying How the Curve Information Impacts on the Driver Performance with Cognition Model. (19th February 2013) - Zhao, Xiaohua; Guan, Wei; Liu, Xiaoming
Abstract : Drivers' misjudgment is a significant issue for the curve safety. It is considered as a more influential factor than other traffic environmental conditions for inducing risk. The research suggested that the cognition theory could explain the process of drivers' behavior at curves. In this simulator experiment, a principle cognition model was built to examine the rationality of this explanation. The core of this pilot study was using one of the driving decision strategies for braking at curves to verify the accuracy of the cognition model fundamentally. Therefore, the experiment designed three treatments of information providing modes. The result of the experiment presented that the warning information about curves in advance can move the position of first braking away from curves. This phenomenon is consistent with the model's inference. Thus, the conclusion of this study indicates that the process of the drivers' behavior at curves can be explained by the cognition theory and represented by cognition model. In addition, the model's characteristics and working parameters can be acquired by doing other research. Then based on the model it can afford the advice for giving the appropriate warning information that may avoid the driver's mistake.